2019
DOI: 10.1371/journal.pone.0218947
|View full text |Cite
|
Sign up to set email alerts
|

Practice and predictors of self-care behaviors among ambulatory patients with hypertension in Ethiopia

Abstract: Background Despite the benefits of evidence-based self-care behaviors in the management of hypertension, hypertensive patients have low rate of adherence to the recommended self-care behaviors. Studies related to self-care behaviors among hypertensive patients are limited in Ethiopia. Objective To assess the rate of adherence to self-care behaviors and associated factors among hypertensive patients. Method A cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 63 publications
7
61
1
3
Order By: Relevance
“…3 Likewise, in the Mediterranean region, 26% of the total population is affected by hypertension. 4 In developing countries, such as within the African region, hypertension has become concerning, with Ethiopia reporting an overall prevalence of 19.6%. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Likewise, in the Mediterranean region, 26% of the total population is affected by hypertension. 4 In developing countries, such as within the African region, hypertension has become concerning, with Ethiopia reporting an overall prevalence of 19.6%. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 10 Past studies have shown effectiveness of self-care behaviors in reduction of BP and associated complications, plus escalation of the efficacy of medication and overall health regimes. 4 , 5 , 30 , 36 Given the potential substantial benefits of self-care, novel approaches, and interventions are required to enable a robust and responsive system that can assist in promoting self-care behavior among individuals with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Dari 12 penelitian yang ditinjau beberapa faktor yang mempengaruhi self-care behavior pada klien dengan hipertensi di komunitas. Beberapa faktor yang mempengaruhi self-care behavior seperti faktor personal yang terdiri dari faktor sosio ekonomi, pendidikan, pengetahuan, peningkatan usia, dan persepsi terhadap penyakit (5,6,(11)(12)(13)(14) , self-efficacy yang merupakan kepercayaan seseorang dalam melakukan aktivitas tertentu, termasuk kepercayaan diri untuk melakukan aktivitas saat hambatan muncul (3,6,8,10,15) , dukungan keluarga yang merupakan upaya yang diberikan kepada anggota keluarga, baik moril maupun materiil, sehingga dengan dukungan itu seseorang merasa diperhatikan, mendapat saran, atau kesan yang menyenangkan pada dirinya (3,10,11) , dan spiritualitas yang merupakan pengalaman manusia secara umum dari suatu pengertian akan makna, tujuan dan moralitas (6) .…”
Section: Gambar 1 Diagram Flow Dan Pemilihan Artikelunclassified
“…Faktor personal yang mempengaruhi self-care behavior adalah status sosio ekonomi,pendidikan, pengetahuan, peningkatan usia dan persepsi terhadap penyakit. status sosio ekonomi,pendidikan, pengetahuan, peningkatan usia dan persepsi secara signifikan mempengaruhi self-care behavior pada klien dengan hipertensi (5,12,14) .…”
Section: Pembahasanunclassified
See 1 more Smart Citation